Omid Safi’s Concept of Progressive Muslims - Nur Hadi Ihsan; Dhita Ayomi Purwaningtyas (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2019)
Omid Safi is a professor of classical and contemporary Islamic studies in North America. His thought influences the contemporary Islamic discourses. It is progressive Muslims, which becomes a new paradigm after liberal Islam. Actually, both of these discourses are almost the same, but Safi tries to present progressive Muslims as a discourse different from liberal Islam. Later, Safi’s concept of progressive Muslims can inspire many Muslim scholars in the West. This study concludes that according to Omid Safi, progressive Muslims come from the spirit of renewal Islam and response to modernity. But after research and comparison from many aspects, progressive Muslims are doing a progressive ijtihad and interpretation to show the humanist Islam and tolerant for social issues by engaging both of tradition and modernity as the main characters. The researcher finally concludes that this discourse is redefining Islam in the manner as other several contemporary Islamic discourses, like liberal Islam and neo-modernism did.